Tumor organoids: From inception to future in cancer research. (10th July 2019) - Yang, Liang; Yang, Shuo; Li, Xinyu; Li, Bowen; Li, Yan; Zhang, Xiaodong; Ma, Yingbo; Peng, Xueqiang; Jin, Hongyuan; Fan, Qing; Wei, Shibo; Liu, Jingang; et al.
Abstract: Tumor models have created new avenues for personalized medicine and drug development. A new culture model derived from a three-dimensional system, the tumor organoid, is gradually being used in many fields. An organoid can simulate the physiological structure and function of tissue in situ and maintain the characteristics of tumor cells in vivo, overcoming the disadvantages of traditional experimental tumor models. Organoids can mimic pathological features of tumors and maintain genetic stability, making them suitable for both molecular mechanism studies and pharmacological experiments of clinical transformation. In addition, the application of tumor organoids combined with other technologies, such as liquid biopsy technology, microraft array (MRA), and high-content screening (HCS), for the development of personalized diagnosis and cancer treatment has a promising future. In this review, we introduce the evolution of organoids and discuss their specific application and advantages. We also summarize the characteristics of several tumor organoids culture systems. Highlights: The arrival of organoids witnessed the emergence of a new era in vitro model. Tumor organoids possess the advantages of gene stability, heterogeneity and pathological features of the primary tumors. Tumor organoids have specific applications in basic research, regenerative medicine and personalized medicine. The pathway of Wnt, BMP and ROCK can regulate the growth of tumor organoids.